Social Media Pressure in Marriage: A Critical Review - Dedek Nur Annisa; Dinda Meliasari; Shofi Aulia Rahma Rambe; Tessalonika Christmas; Hairani Siregar (Lembaga Yasin AlSys, 2026)
The rapid expansion of social media in Indonesia, with 139 million active users spending more than three hours online daily, has increasingly blurred the boundary between private marital life and public spectacle. This condition has intensified digital jealousy, social comparison, and dramaturgical self-presentation, which may strain relationship quality and shape young people’s perceptions of marriage. This study aims to analyze social media pressures on marital dynamics among Indonesia’s younger generation, particularly Gen Z and millennials, by drawing on Goffman’s dramaturgical theory to examine mechanisms related to idealized expectations, negative marital narratives, and relational conflict. Using a qualitative descriptive approach, this study conducted a systematic literature review of secondary sources published between 2016 and 2026, including journals, books, and reports. The data were analyzed through content analysis involving open, axial, and selective coding, with triangulation used to strengthen validity. The findings indicate that social media amplifies upward comparison through curated “front-stage” representations of marital harmony, while digital jealousy, phubbing, and cyber-infidelity contribute to declining trust and relational dissatisfaction. Negative viral content also appears to delay marriage commitments among younger generations. Intensive social media use is associated with a 15% decline in marital satisfaction and increasing divorce trends, although media literacy and family values function as important moderating factors. The study concludes that social media pressures pose a growing challenge to family institutions, yet targeted interventions, including digital literacy, premarital counseling, and the promotion of realistic relational content, may help mitigate these risks. The study contributes to family sociology and digital society literature by clarifying how online visibility, comparison, and mediated interaction reshape contemporary marital expectations and relationship stability.